Epidemiology, genetic diversity and symptom characterization of rotavirus infection in Saudi Arabia, 1985–2024: a meta-analysis - Alzahrani, Khalid J. (Frontiers in Microbiology, 2025)
IntroductionRotavirus infection has been a major health burden among children under 5 years in Saudi Arabia. There is a lack of meta-analysis on epidemiology and genetic diversity of rotavirus in Saudi Arabia.MethodsWe conducted this study to provide a comparative overview of rotavirus infection in Saudi Arabia. We selected published literature between 1985 and 2025.ResultsEpidemiological data were retrieved from 18 articles. In Saudi Arabia, the pooled prevalence of RVA among children under 5 years was 34.3% (95% CI: 2% to 81%, I2 = 98.97%). Overall, G1P[8] (52%, 95% CI: 29% to 69%, I2 = 0%) was reported from the highest number of cases, followed by G2P[4] (18%, 95% CI: 9% to 31%, I2 = 36.86%), G9P[8] (14%, 95% CI: 8% to 27%, I2 = 45.37%), G12P[8] (4%, 95% CI: 2% to 11%, I2 = 0%), and G3P[8] (3%, 95% CI: 1% to 11%, I2 = 99%), respectively. Genotype G2P[4] (41%) became the most prevalent, while the frequency of G1P[8] reduced to 38% and G9P[8] to 6% during 2013–2024. The odds of rotavirus infection increased in the winter season (aOD 2.4, 95% CI: 1.52 to 3.57, p-value 0.005). The odds of rotavirus prevalence were significantly lower after vaccination (aOD 0.56, 95% CI: 0.25 to 0.73, p-value 0.001).DiscussionThis is one of the first meta-analyses to compare the genotypic data of rotaviruses before and after vaccination in Saudi Arabia. This study will provide an overall insight into prevalence, genetic diversity, and seasonality during pre-vaccination and post-vaccination periods and contribute to policy making.